2012
DOI: 10.1100/2012/616430
|View full text |Cite
|
Sign up to set email alerts
|

Uranium in the Surrounding of San Marcos-Sacramento River Environment (Chihuahua, Mexico)

Abstract: The main interest of this study is to assess whether uranium deposits located in the San Marcos outcrops (NW of Chihuahua City, Mexico) could be considered as a source of U-isotopes in its surrounding environment. Uranium activity concentrations were determined in biota, ground, and surface water by either alpha or liquid scintillation spectrometries. Major ions were analyzed by ICP-OES in surface water and its suspended matter. For determining uranium activity in biota, samples were divided in parts. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…For instance, Lepomis cyanellus : . From results of Table 3, uranium activity concentrations present in fish fillet are low, in comparison with both the reference values established by UNSCEAR 2008 [57], and the values of 0.14–2.6 and 0.6–4.5 Bq∙kg −1 (dry weight) for 238 U and 234 U, respectively, reported in samples of species Cichlasoma labridens in San Marcos Dam (Chihuahua) [33]. The uranium concentrations found in this study are also lower than those presented in other publications related with uranium mine activities [58,59].…”
Section: Resultsmentioning
confidence: 74%
“…For instance, Lepomis cyanellus : . From results of Table 3, uranium activity concentrations present in fish fillet are low, in comparison with both the reference values established by UNSCEAR 2008 [57], and the values of 0.14–2.6 and 0.6–4.5 Bq∙kg −1 (dry weight) for 238 U and 234 U, respectively, reported in samples of species Cichlasoma labridens in San Marcos Dam (Chihuahua) [33]. The uranium concentrations found in this study are also lower than those presented in other publications related with uranium mine activities [58,59].…”
Section: Resultsmentioning
confidence: 74%
“…In addition, in the San Marcos area, located NW of Chihuahua City, there are two uranium mineral outcrops [ 17 ]. Previous studies have demonstrated that this area shows higher radioactivity levels in surface water, sediments and biota [ 18 ]. Likewise, the authors have found that there is mobility of the uranium by surface and ground water from the San Marcos area to the low levels of the Chihuahua valley [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geographical references of uranium outcrops provided from a group of experts in Mexico (Mx) and others mentioned in the bibliography [3,4,7,21] were used as the second database.…”
Section: Datamentioning
confidence: 99%
“…The exploration and exploitation of uranium ores in Chihuahua, Mexico, took place in the decades of [1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980], by the enterprise Uranio de Mexico (URAMEX). Although there has not been commercial production of uranium in Mexico, in Chihuahua State there are several uranium outcrops and radioactive anomalies, which led Chihuahua to be known as the "uranium province" [1,2,3,4,5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%